Deciphering the regulatory mechanisms of potato cold-induced sweetening via integrated time-course transcriptome and metabolome analysis - Cui, Guangcan; Zhou, Tingting; Liu, Zhongliang; Wang, Ting; Wang, Qingguo; Liu, Tengfei (Frontiers in Plant Science, 2025)
Cold-induced sweetening (CIS) in potatoes is a significant challenge affecting the quality and marketability of processed potato products. This study aims to decipher the regulatory mechanisms underlying CIS through integrated time-course transcriptome and metabolome analysis. Freshly harvested potato tubers (Solanum tuberosum L. cv. ‘Netherlands No. 15’) were stored at 4°C and 20°C for various durations. RNA sequencing and quantitative real-time PCR were employed to analyze gene expression changes, while metabolomic profiling was conducted using UHPLC-MS/MS. Our results reveal significant alterations in carbohydrate metabolism, with a marked increase in reducing sugars during cold storage. Critical enzymes involved in starch degradation, such as β-amylases (StBAM1, StBAM9), and sucrose metabolic genes (StUGPase2, StVInv) were upregulated, while starch synthesis genes were downregulated. Co-expression analysis identified potential transcription factors, including StHSFA2 and StAPRR2, which may regulate these metabolic pathways. Functional assays demonstrated that StHSFA2 significantly activates the promoters of StBAM1 and StUGPase2, while StAPRR2 shows specific activation of the StVInv enhancer. These findings suggest distinct but complementary roles for StHSFA2 and StAPRR2 in regulating starch degradation and sucrose metabolism during CIS. This comprehensive analysis provides insights into the molecular mechanisms of CIS and identifies potential targets for genetic manipulation to mitigate its effects, thereby enhancing the storage quality and processing performance of potatoes.